The Effect of Quranic and Hadith-Based Animated Video Media on the Understanding of Science Concepts in Fourth Grade Elementary School Students - Liza Septiani; Mega Adyna Movitaria; Wisda Rahmadinur; Zulkipli Lessy (Suluah Pasaman, 2026)
This research was motivated by students' low conceptual understanding of science subjects, which fell below the minimum grade point average (KKTP), namely 64 out of a standard of 70. The study aimed to determine the effect of using animated video media based on the Quran and Hadith on the conceptual understanding of science subjects in fourth-grade elementary school students. The method used was a quasi-experimental design with a one-group pre-test and post-test, with a sample of 29 students using saturated sampling. Data analysis included validity, reliability, normality, and homogeneity tests, as well as hypothesis testing using t-tests and simple linear regression. The results showed a t-test significance of 0.000 < 0.05 and a calculated t-value of 11.352 > t-table of 1.699, with a coefficient of determination (R²) of 0.632 (63.2%). The average student score increased from 64 to 82.4, with a learning completion rate of 89.7% (≥ 70). Thus, animated video media based on the Quran and Hadith has been proven effective in improving elementary school students' understanding of science concepts